2019
DOI: 10.1001/jamanetworkopen.2019.2619
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Exposure and Mental Health Among Puerto Rican Youths After Hurricane Maria

Abstract: Importance Quantifying the magnitude of disaster exposure and trauma-related symptoms among youths is critical for deployment of psychological services in underresourced settings. Hurricane Maria made landfall in Puerto Rico on September 20, 2017, resulting in massive destruction and unprecedented mortality. Objective To determine the magnitude of disaster exposure and mental health outcomes among Puerto Rican youths after Hurricane Maria. Design, Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 38 publications
1
94
1
3
Order By: Relevance
“…Psychological disorders may also develop following ecological disasters, produce significant morbidity and mortality, and require healthcare interventions. The most studied is Posttraumatic Stress Disorder (19,20), along with depression (21,22) and anxiety (22,23). A study of residents in Mexico 2 months after the September 2017 earthquake revealed 36.4% indicating symptoms consistent with PTSD, with increased risk found in women, those who had home damage, and indigenous people (24).…”
Section: Psychological and Behavioral Effectsmentioning
confidence: 99%
“…Psychological disorders may also develop following ecological disasters, produce significant morbidity and mortality, and require healthcare interventions. The most studied is Posttraumatic Stress Disorder (19,20), along with depression (21,22) and anxiety (22,23). A study of residents in Mexico 2 months after the September 2017 earthquake revealed 36.4% indicating symptoms consistent with PTSD, with increased risk found in women, those who had home damage, and indigenous people (24).…”
Section: Psychological and Behavioral Effectsmentioning
confidence: 99%
“…The Internet has had a very important role in the activation and maintenance of these links, as extra-official response to the crisis could begin soon after the Hurricane, and traditional arts and crafts can be offered and sold in spite of damage to the physical shops where they had been usually marketed. At the same time, the unending crisis, the failure to restore power and water to thousands of people, the damaged infrastructure, the destroyed houses exposing thousands to habitat insecurity, the lack of federal and local help, and the mass migration extending livelihood insecurity to the mainland, continues to undermine Puerto Rican mental and social health as well as grassroots recovery efforts given that the magnitude of the need is so overwhelming that all help seems insignificant (Orengo-Aguayo, Stewart, de Arellano, Suárez-Kindy, & Young, 2019;Scaramutti, Salas-Wright, Vos, Schwartz, 2019).…”
mentioning
confidence: 99%
“…Comparison samples of Puerto Ricans who stayed versus those who migrated to the U.S. mainland showed very high rates of depression and PTSD in both groups but significantly higher rates for those who relocated (13). A nationwide survey of 96,000 Puerto Rican students found that 7% had symptoms compatible with PTSD (14). Furthermore, 45% sustained home damage (25% were displaced), and about one-third perceived personal life threat during the storm.…”
Section: Lessons Learned From Recent North Atlantic Hurricanesmentioning
confidence: 99%